Promoting inter-religious harmony through university-community engagement project: a case study of the educational visit to places of worship (EDVIST) - Mohd Nor, Nur Suriya (2019)
Background: National integration is one of the Malaysian Core Values i.e. Core Value 3. It can be achieved by multi-religious, multi-ethnics and multi-cultural Malaysia through the bonds that unify all Malaysians. The integration depends on the various communities coming together to live with mutual understanding, tolerance, and acceptance of diversity. In promoting the unity among multi-religious society Malaysia, the Department of Usul al-Din and Comparative Religion (RKUD), Kulliyyah Islamic Revealed Knowledge and Human Science (KIRKHS), International Islamic University Malaysia (IIUM) conducting a University-Community Engagement (UCE) project known as the Educational Visit to Places of Worship (EDVIST). This project is a platform to promote inter-religious harmony among Malaysians. The visit is planned as part of study tour for undergraduate students attending classes of World Religions 1 and 2 in every semester (Semester 1 and Semester 2). The purpose of the visit is to give exposure to the students to religions in Malaysia i.e. Christianity, Hinduism, Buddhism, Sikhism, and Chinese Religions. The activities during this visit include tour of the house of worship and dialogues.